PENGEMBANGAN TEKNOLOGI ENKAPSULASI UNTUK MENINGKATKAN PERFORMA BETON SELF-HEALING MICROBIAL: TINJAUAN LITERATUR SISTEMATIS - Dewi ayu setiawati; Andi Arham Adam; I Nengah Suastika (Jurnal Sains dan Teknologi Tadulako, 2026)
Microbial self-healing concrete offers an innovative solution to address the problem of cracks in modern infrastructure, but its field application is hindered by the viability of bacteria within the harsh concrete matrix. This systematic literature review aims to explore the development of encapsulation technology as a strategy to enhance the performance of microbial self-healing concrete. The methodology includes a comprehensive search of major academic databases using a combination of specific keywords, and article selection based on strict inclusion and exclusion criteria. Analysis found that a diverse range of encapsulation technologies have been adopted, including the use of sodium silicate-coated Recycled Coarse Aggregate (RCA), fly ash, cement shell microencapsulation, biopolymer encapsulation, pH-sensitive hydrogels, and modified manufactured aggregates. These technologies significantly enhance bacterial viability and the effectiveness of the self-healing process, resulting in more efficient crack closure and improved mechanical properties and durability of the concrete. Nevertheless, significant challenges still include the long-term viability of bacteria, limitations in the scale of field application, and the high cost of encapsulation production. Future research prospects focus on developing more robust bacterial strains, more economical encapsulation strategies, comprehensive field-scale validation, and integration with sustainable materials and machine learning for design optimization. This research concludes that the development of essential encapsulation technology is crucial in advancing microbial self-healing concrete applications toward more durable and environmentally friendly construction solutions.